2021
DOI: 10.1101/2021.09.01.21262994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cross-sectional Study on Perceived Workplace Health Support and Health-Related Quality of Life

Abstract: Objective: Many companies in Japan have been increasingly interested in "health and productivity management (H&PM)." In terms of H&PM, we supposed that companies can enhance their employees' perceived workplace health support (PWHS) by providing support for workers' lively working and healthy living. This could then improve health-related QOL (HRQOL) by increasing PWHS. This study explored the relationship between PWHS and health-related quality of life (HRQOL). Methods: During the COVID-19 pandemic i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…28 A previous study has reported that during the COVID-19 pandemic, the higher workers’ perceived workplace health support—that is, the support for workers’ lively working and healthy living provided by the workplace—the higher the health-related quality of life. 29 In addition, clear policies surrounding workplace IPC measures have been reported to build trust between employers and workers. 30 Actively promoting workplace IPC measures could also be found to enhance corporate governance, increase employees’ perceived workplace health support, and contribute to positive mental health, including increased work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…28 A previous study has reported that during the COVID-19 pandemic, the higher workers’ perceived workplace health support—that is, the support for workers’ lively working and healthy living provided by the workplace—the higher the health-related quality of life. 29 In addition, clear policies surrounding workplace IPC measures have been reported to build trust between employers and workers. 30 Actively promoting workplace IPC measures could also be found to enhance corporate governance, increase employees’ perceived workplace health support, and contribute to positive mental health, including increased work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Infection control in the workplace, which is where workers spend most of their time and therefore a major place of human contact, has been reported to affect not only infection prevention but also workers' mental well-being and performance. [9][10][11][12] COVID-19 measures taken by Japanese employees include refraining from going to work when sick, measuring their body temperature, disinfecting the workplace, and teleworking. However, the extent to which the various control measures are implemented varies with the size of the company, the type of work, and other factors.…”
Section: Introductionmentioning
confidence: 99%